2021
DOI: 10.3892/ol.2021.12449
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of risk factors for lymph node metastasis in patients with papillary thyroid carcinoma

Abstract: With the increasing incidence of papillary thyroid cancer (PTC), it is important to risk-stratify patients who may have a more aggressive tumor biology. The present study aimed to evaluate the risk factors for lymph node metastasis (LNM) in patients with PTC, which may provide a significant reference for clinical diagnosis and treatment. In total, 1,045 patients with PTC [313 with PT microcarcinoma (PTMC) and 732 with non-PTMC] between August 2016 and August 2019 were investigated. The B-type Raf kinase (BRAF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Multivariate Cox regression analysis in this study found that older age, larger tumor size, upper pole location, and capsular invasion were independent factors of the SLNM development. Older age is a risk factor for both PTC [17][18][19] and LLNM. 20,21 Wang et al concluded that age ≥55 years was an independent risk factor for SLNM, which is consistent with the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate Cox regression analysis in this study found that older age, larger tumor size, upper pole location, and capsular invasion were independent factors of the SLNM development. Older age is a risk factor for both PTC [17][18][19] and LLNM. 20,21 Wang et al concluded that age ≥55 years was an independent risk factor for SLNM, which is consistent with the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid cancer is the most frequently occurring endocrine cancer in China and has the fastest increase in incidence [ 1 , 2 ]. At present, surgery is the essential method of curing thyroid cancer, especially papillary thyroid carcinoma, which is the most common pathological type [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%